PEMBUDIDAYAAN JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) DENGAN MEDIA LIMBAH KAYU - Sihati Suprapti (Jurnal Penelitian Hasil Hutan, 1987)
Wood waste such as sawdust, leaves of legume plants  such as turi (Sesbania  grandiflora  Pers.) and lamtoro  gung (Leucaena   leucocephala (Lam.)  de Wit.)  were used as substrates for  oyster mushroom,  Pleurotus  ostreatus  cultivation. The substrate consisted of rubber wood sawdust (Hevea brasiliensis Muell. Arg.) mixed  with turi  or lamtoro gung leaves containing  50%, 100%, 150%, 200%, by weight and distilled  water. The substrate was allowed to cool after autoclave sterilization  before  being inoculated  with pure  culture oyster  mushroom.The mushroom was harvested  every day after  the growth  of the fruiting body. The average yield  of  the entire  treatments  was 643.00 g (532. 29- 744. 69 g) per kg of dry weight of substrate.  The highest product  was obtained from  rubber wood sawdust substrate  mixed  with 10% turi leaf.